2021
DOI: 10.1523/eneuro.0561-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Selective Overexpression of Collybistin in Mouse Hippocampal Pyramidal Cells Enhances GABAergic Neurotransmission and Protects against PTZ-Induced Seizures

Abstract: Collybistin (CB) is a rho guanine exchange factor found at GABAergic and glycinergic postsynapses that interacts with the inhibitory scaffold protein, gephyrin, and induces accumulation of gephyrin and GABA A receptors (GABA A Rs) to the postsynapse. We have previously reported that the isoform without the src homology 3 (SH3) domain, CBSH3-, is particularly active in enhancing the GABAergic postsynapse in both cultured hippocampal neurons as well as in cortical pyramidal neurons after chronic in vivo expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Enhancement of GABAergic neuro-transmission has been shown to inhibit or attenuate seizures. 37 GABA is mainly synthesized at axonal terminals, which is formed by decarboxylate of glutamate precursor under the action of glutamic acid decarboxylase (GAD). Synthetic GABA is released from vesicles into the synaptic cleft via vesicular GABA transporters after neuron depolarization.…”
Section: Abnormal Ion Channel Functionmentioning
confidence: 99%
“…Enhancement of GABAergic neuro-transmission has been shown to inhibit or attenuate seizures. 37 GABA is mainly synthesized at axonal terminals, which is formed by decarboxylate of glutamate precursor under the action of glutamic acid decarboxylase (GAD). Synthetic GABA is released from vesicles into the synaptic cleft via vesicular GABA transporters after neuron depolarization.…”
Section: Abnormal Ion Channel Functionmentioning
confidence: 99%
“…Studies in CB knockout mice revealed that loss of CB results in severe disruption to the clustering of gephyrin and GABA A receptors in certain brain regions, including the hippocampus (Papadopoulos et al, 2008). Overexpression of CB2SH3 in specific neuron types enhances postsynaptic accumulation of gephyrin, GABA A receptors, and GABAergic synaptic transmission in the developed hippocampus (George et al, 2021).…”
Section: Collybistin (Cb)mentioning
confidence: 99%
“…Previously these investigators demonstrated the relevance of α2 subunit interactions with collybistin by showing that disruption of α2/collybistin interactions made mice susceptible to seizures and early death ( Hines et al, 2018 ). In recent years, the importance of collybistin, encoded by Cdc42 Guanine Nucleotide Exchange Factor 9 (ARHGEF9), to functional inhibitory synapses has become clear with the discovery of multiple patients with ARHGEF9 mutations that present with disease syndromes including epilepsy ( Shimojima et al, 2011 ; George et al, 2021 ; Hines et al, 2022 ). Additionally, a recent study in mice demonstrated that increased expression of collybistin results in elevated GABAergic signaling and mitigates the development of seizures in an SE model ( George et al, 2021 ).…”
Section: Inhibitory Synapse Formation and Eliminationmentioning
confidence: 99%